Foreword - Lukács, János (Public Finance Quarterly, 2025)
The publication of this issue of our journal marks the 200th anniversary of István Széchenyi’s ﬁrst speech in Hungarian at the upper house of the Diet of Pozsony, which marked the beginning of the Reform Era. Three weeks later, in his speech to the lower house, he oﬀered the annual income from his estates to establish a scientiﬁc society, which would later become the Hungarian Academy of Sciences, an institution that has remained the foremost guardian of our national identity ever since.